Two-Year Outcome of Repeat Trabeculectomy with Mitomycin C in Primary Open-Angle and PEX Glaucoma. Issue 3 (May 2015) - Meyer, Linda M.; Graf, Natascha E.; Philipp, Sebastian; Fischer, Marie T.; Haller, Katharina; Distelmaier, Peter; Schönfeld, Carl-Ludwig
Purpose: To evaluate the effectiveness of repeat trabeculectomy with risk factor–adjusted mitomycin C (MMC) application in primary open-angle glaucoma (POAG) and pseudoexfoliation glaucoma (PEXG) over 2 years. Methods: A total of 58 patients (43 with POAG, 15 with PEXG) who had undergone repeat trabeculectomy with MMC were included in this retrospective study. Exposure time of MMC 0.3 mg/mL was adjusted according to a standardized protocol. Main outcome measures were best-corrected visual acuity (BCVA), intraocular pressure (IOP) reduction, surgical success rate (criteria were defined as A: IOP ≤21 mm Hg and a reduction of IOP ≥20%; B: IOP ≤18 mm Hg and a reduction of IOP of ≥30%; C: IOP ≤15 mm Hg and a reduction of IOP of ≥40% from baseline), and number of medications at baseline, 3 months, and 2 years postoperatively. Results: The BCVA remained stable for 2 years after surgery (0.47 ± 0.47 at baseline, 0.49 ± 0.64 logMAR units after 2 years, respectively). Mean IOP decreased from 22.2 ± 7.0 mm Hg at baseline to 12.7 ± 3.1 mm Hg at 3 months and 12.9 ± 4.3 mm Hg 2 years after surgery. The qualified success rate for criterion A was 75.4%, for criterion B 66.6%, and for criterion C45.6%. Complete success rates were 42.9%, 37.5%, and 32.1%, respectively. Two years after repeat trabeculectomy, the mean IOP was reduced by 38.8%, and the number of medications was reduced significantly. Conclusions: Repeat trabeculectomy with MMC is successful at lowering IOP in POAG and PEXG and permits a significant and safe reduction of antiglaucomatous medication for at least 2 years after surgery.